(untitled) (American Scholar: Journal of Interdisciplinary Research and Knowledge, 2026)
This article discusses the pedagogical importance of organizing a gamebased learning environment in teaching parts of speech to 3rd-grade students. It analyzes how didactic games contribute to improving students’ grammatical competence, cognitive activity, and communication skills. The article also presents specific examples of educational games and their effectiveness in classroom practice.